UPAYA GURU DALAM MENINGKATKAN KETERAMPILAN MOTORIK HALUS ANAK MELALUI KEGIATAN MERONCE PADA ANAK KELOMPOK A1 DI RA SYIHABUDDIN KOTA MALANG - Nurlaila La Dana; Devi Wahyu Ertanti; Ika Anggraheni (UNISMA, 2020)
Based on the results of the initial observation on Friday, October 4, 2019 at RA Syihabuddin, Landungsari, Malang, that the fine motor skills of the A1 group had not yet developed. 2. So in this case, researchers intend to conduct research, namely about the activities of meronce in improving children's fine motor skills, teacher efforts in improving child's fine motor skills through meronce activities, and the learning outcomes of children through the activities of the A1 group Meronce in RA Syihabuddin. In this study, researchers used a qualitative approach and type of case study research. In this study researchers collected the data using interview techniques. In this study, the results obtained from the testimony of the Ustadzah Sulfi Rosyidaturrohmah which can be concluded that a PAUD / RA that almost all children have been able to do meronce activities in the class without teacher assistance.